Peripheral edema in a child with a new diagnosis of insulin-dependent diabetes mellitus - Zamir, Imran; Zubairu, Abdullahi; Cainer, Amanda; Jagwani, Harshita (Indian Journal of Case Reports, 2024)
Peripheral or generalized edema is an uncommon complication of insulin therapy in diabetes mellitus. The exact cause is yet not known. It is transient and self-limiting in nature. However, diuretics and aldosterone antagonists have been used in some cases. We report the case of a 14-year-old boy with newly diagnosed Type 1 diabetes who developed edema after the commencement of insulin therapy. Other causes of edema were excluded from the study. The child was managed conservatively and edema seemed to start decreasing after 72 h and completely disappear in 2 weeks.